EFFECTIVENESS ANALYSIS OF SAKTI APPLICATION IN SUPPORTING STATE FINANCIAL DISBURSEMENT AT BPOM IN 2024 - Christiningrum, M. F.; Muhamad Jihan Naslin (Institut Bisnis Nusantara, 2025)
This study evaluates the effectiveness of the Sistem Aplikasi Keuangan Tingkat Instansi (SAKTI) in facilitating state financial disbursement at the Indonesian Food and Drug Authority (BPOM) in 2024, focusing on the role of user operators. Utilizing the DeLone and McLean Information Systems Success Model (2003), the study examines the influence of System Performance (SP), Information Effectiveness (IE), and Service Performance (SV) on SAKTI’s Net Benefit Effectiveness (NB). Employing Partial Least Square Structural Equation Modeling (PLS-SEM) with data from 18 user operator respondents collected via a Likert-scale questionnaire, the findings reveal that System Performance significantly impacts Net Benefit Effectiveness (path coefficient = 0.651, P = 0.025, f² = 0.508). In contrast, Information Effectiveness (path coefficient = -0.024, P = 0.479, f² = 0.000) and Service Performance (path coefficient = 0.247, P = 0.256, f² = 0.040) show no significant influence. The model explains 69.8% of the variance in Net Benefit Effectiveness (R² = 0.698). Challenges such as complex system features and limited training are identified. Recommendations include enhancing system reliability, simplifying interfaces, and providing regular training to optimize SAKTI’s effectiveness.